EFFECT OF INTEGRATED NUTRIENT MANAGEMENT PRACTICES ON YIELD ATTRIBUTES AND YIELD OF BABY CORN IN BABY CORN (Zea mays. L) - HYACINTH BEAN (Lablab purpureus var typicus) CROPPING SYSTEM. - T. RAM PRAKASH, R. PREETHAM, K. AVIL KUMAR, A. SRINIVAS, A. MANOHAR RAO and (The Journal of Research, PJTSAU, 2019)
A field experiment was conducted at Horticultural Research Station, Adilabad during kharif, 2015 and 2016 and rabi seasons of 2015-16 and 2016-17 to study the effect of integrated nutrient management practices on yield attributes and yield of baby corn in baby corn-hyacinth bean cropping system. The experiment was laid out in a randomized block design for baby corn during kharif, 2015 season with seven treatments comprised of T1: 25% N through FYM + 75% RDF (Recommended dose of fertilizer), T2: 25% N through FYM + 75% RDF + Azospirillum and Bacillus megaterium @ 5 kg ha-1 each, T3: 25% N through vermicompost + 75% RDF, T4: 25% N through vermicompost + 75% RDF + Azospirillum and Bacillus megaterium @ 5 kg ha-1 each, T5: 100% RDF, T6: 100% RDF + Azospirillum and Bacillus megaterium @ 5 kg ha-1 each, T7: Control (No fertilizer application) replicated thrice. Each main treatment is sub divided into four sub plots and the treatments S1-100% RDF, S2-75% RDF, S3-100% RDF + Bradyrhizobium @ 500 g ha-1 (seed treatment) and S4-75% RDF + Bradyrhizobium @ 500 g ha‑1 (seed treatment), were imposed for hyacinth bean in rabi season and data of kharif, 2016 was analyzed in split plot design. All the treatments (organic, inorganic sources of nutrition in conjunction with bio-fertilizers) showed significantly higher number of cobs plant-1, cob length, cob girth, cob width, cob weight with or without husk and yield over un-fertilized control. Among the different treatments, application of 75% RDF integrated with 25% RDN through vermicompost in conjunction with bio-fertilizers recorded significantly higher number of cobs plant -1 (2.23 and 2.22), cob length (12.50 and 12.24 cm), cob girth (5.74 and 5.65 cm), cob width (1.86 and 1.83 cm), cob weight without husk (13.46 and 12.06 g), cob yield with husk (12290 and 11727 kg ha-1), cob yield without husk (2049 and 1890 kg ha-1) and stover yield (24020 and 21165 kg ha-1) during kharif, 2015 and 2016, respectively. Application of 100% RDF along with seed treatment with Bradyrhizobium to hyacinth bean crop during rabi 2015-16 resulted in significantly higher baby cob weight without husk (9.95 g) in succeeding kharif, 2016 over 100% RDF, 75% RDF and 75% RDF + seed treatment with Bradyrhizobium.